Smart Mirror - AL-Hashlamoon, Dalah; Abu Hussein, Morjana (جامعة بوليتكنك فلسطين - امن معلومات, 2025)
Traditional mirrors are no longer sufficient to meet the growing demand for convenience and connectivity in modern homes. The integration of advanced technologies into daily routines has transformed everyday objects into multifunctional smart devices, offering enhanced utility and user experience. This project proposes the development of a Smart Mirror—a modernized mirror integrated with intelligent functionalities to assist users in their daily activities. The smart mirror system incorporates various features such as real-time weather updates, calendar synchronization, voice interaction, and personalized notifications. It also integrates a mobile application to allow seamless connectivity, enabling users to share photos via QR code. Additionally, the smart mirror supports environmental sensors for temperature, humidity, and brightness adjustments, along with a unique outfit color matching feature to provide users with suggestions on suitable outfit combinations, enhancing convenience and user interaction with dynamic displays and intuitive control. Keywords: Smart Mirror, Home Automation, Voice Interaction, Machine Learning and AI, Outfit Color Matching.
no of pages 73, امن معلومات 1/2025
Keywords: Smart Mirror